Thesarus Lex: En ny svensk elektroniskt länkad thesaurus - Lange, Sven; Törnqvist, Lars (Nordiske Studier i Leksikografi, 2003)
In this article, we present our plans of creating a Swedish electronic thesaurus, containing words and phrases classified according to Roget’s Thesaurus. The new electronic thesaurus is intended to be the spider in a web of various types of hyperlinked lexicographic products, e.g. monolingual and bilingual dictionaries, historical dictionaries and encyclopedic databases.